PML–RARα induces all-trans retinoic acid-dependent transcriptional activation through interaction with MED1. Issue 3 (27th May 2019) - Fukuoka, Tomoya; Kawai, Asami; Takahara, Taku; Mori, Mahiro; Roeder, Robert G.; Hasegawa, Natsumi; Ito, Mitsuhiro
ABSTRACT: Transcriptional activation by PML–RARα, an acute promyelocytic leukemia-related oncofusion protein, requires pharmacological concentrations of all-trans retinoic acid (ATRA). However, the mechanism by which the liganded PML–RARα complex leads to the formation of the preinitiation complex has been unidentified. Here we demonstrate that the Mediator subunit MED1 plays an important role in the ATRA-dependent activation of the PML–RARα-bound promoter. Luciferase reporter assays showed that PML–RARα induced significant transcription at pharmacological doses (1 μM) of ATRA; however, this was submaximal and equivalent to the level of transcription driven by intact RARα at physiological doses (1 nM) of ATRA. Transcription depended upon the interaction of PML–RARα with the two LxxLL nuclear receptor recognition motifs of MED1, and LxxLL→LxxAA mutations led to minimal transcription. Mechanistically, MED1 interacted ATRA-dependently with the RARα portion of PML–RARα through the two LxxLL motifs of MED1. These results suggest that PML–RARα initiates ATRA-induced transcription through its interaction with MED1.